2017
DOI: 10.1016/j.foodhyd.2016.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale properties of biopolymer multilayers

Abstract: Layer by Layer (LbL) deposition is a simple and inexpensive method of multilayer self-assembly, that relies on the electrostatic interactions of oppositely charged polyelectrolytes. Functional biopolymers used to build such nanostructured multilayers can keep serving their inherent functions in food systems. A good example is chitosan, a positively charged biopolymer which has antimicrobial properties and forms stable complexes with negatively charged polymers. This study investigates the potential of commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, pectin is easily available and cheap due to it is a byproduct or waste product of fruit juice manufacture . Gezgin et al reported that pectin properties vary with the degree of methyl esterification, being classified as high methyl esterification pectin (HDM) or low methyl esterification pectin. Thus, it has several applications due to its gelling agent capacity, besides to be biocompatible, biodegradable, and nontoxic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pectin is easily available and cheap due to it is a byproduct or waste product of fruit juice manufacture . Gezgin et al reported that pectin properties vary with the degree of methyl esterification, being classified as high methyl esterification pectin (HDM) or low methyl esterification pectin. Thus, it has several applications due to its gelling agent capacity, besides to be biocompatible, biodegradable, and nontoxic.…”
Section: Introductionmentioning
confidence: 99%
“…Its main commercial sources are peel and pulp of citrus fruits and apples, due to the fact that it is a byproduct of the production of juices and jams (Chakravartula et al, 2019;de Castro e Silva et al, 2020;Kadzi nska, Janowicz, Kalisz, Bry s, & Lenart, 2019;Naik, Rawson, & Rangarajan, 2020;Syarifuddin, Manggala, Dirpan, & Laga, 2019). Gezgin, Lee, and Huang (2017) reported that pectin has several properties according to the degree of methyl esterification, being classified as low methylesterification pectin (LMP) or high methylesterification pectin (HMP). The various properties provide various applications as a gelling, thickener, and stabilizer in the food and pharmaceutical industries (Assadpour, Jafari, & Maghsoudlou, 2017;de Castro e Silva et al, 2020;Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A similar work on ice propagation had been conducted using the layer by layer (LbL) deposition of polyelectrolyte pairs PSS/poly(allylamine hydrochloride) (PAH) and PSS/PDDA without using ECINs, where authors concluded that ice propagation can be tuned by modifying the outermost polymer layer (Jin, He, Guo, & Wang, 2017), which in fact was performed in our above cited work by adding a single layer of ECINs on the PSS/PDDA multilayers. We have also demonstrated the potential to fabricate the same using food grade charged biopolymers such as chitosan, carrageenan, and pectin (Gezgin, Lee, & Huang, 2017). Tuning of ice nucleation using ionic polyelectrolyte multilayers such as poly[2‐(methacryloyloxy)‐ethyltrimethylammonium] (PMETA) and anionic poly(3‐sulfopropylmethacrylate) (PSPMA) brush surfaces (He et al., 2016), as well as polyvinyl alcohol (PVA) layers (Wu et al., 2019) have also been reported.…”
Section: Introductionmentioning
confidence: 99%